Międzynarodowa ochrona migrantów klimatycznych – w poszukiwaniu realistycznych rozwiązań - Jakuszewicz, Adam (Polityka i Społeczeństwo, 2020)
Legal scholars have put forward a series of proposals to create a legally binding instrument for the protection of climate migrants. Their implementation, however, is fraught with political obstacles (in particular, the divergence of interest between developed and developing states, the sensitive nature of immigration and climate policies) and legal difficulties (problems with determining the scope of persons eligible for international protection, limited operationality of a universal international treaty for regulating such delicate and contentious matters and, in some instances, procedural obstacles). For these reasons the most effective approach to the issues of international assistance to climate migrants is to promote the perception of this issue as a form of adaptation to the effects of climate change. A helpful instrument that also may prove effective in this respect are multilateral and regional agreements.